A Note on Best Approximation in 0-Complete Partial Metric Spaces. (23rd October 2014) - Demma, Marta; Jleli, Mohamed; Samet, Bessem; Vetro, Calogero
Abstract : We study the existence and uniqueness of best proximity points in the setting of 0-complete partial metric spaces. We get our results by showing that the generalizations, which we have to consider, are obtained from the corresponding results in metric spaces. We introduce some new concepts and consider significant theorems to support this fact.